2015
DOI: 10.1115/1.4031623
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Modeling of an Acoustic Instability in Pilot-Operated Pressure Relief Valves

Abstract: Pressure relief valves (PRVs) are included as an essential element of many compressor piping systems in order to prevent overpressurization and also to minimize the loss of process gas during relief events. Failure of the valve to operate properly can result in excessive quantities of vented gas and/or catastrophic failure of the piping system. Several mechanisms for chatter and instability have been previously identified for spring-loaded relief valves, but pilot-operated relief valves are widely considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Typically, one encounters the first, quarter-wave, harmonic of the pipe -that is a standing wave of wavelength of four times the pipe length. Examples of such vibrations can be found in Allison and Brun (2015), where the authors found that the quarter-wave frequency to dominate valve oscillation. Similarly, in Misra et al (2002) the quarter-wave eigenfrequency of the downstream piping was found to match with the observed vibration frequency.…”
Section: Quarter-wave Instabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, one encounters the first, quarter-wave, harmonic of the pipe -that is a standing wave of wavelength of four times the pipe length. Examples of such vibrations can be found in Allison and Brun (2015), where the authors found that the quarter-wave frequency to dominate valve oscillation. Similarly, in Misra et al (2002) the quarter-wave eigenfrequency of the downstream piping was found to match with the observed vibration frequency.…”
Section: Quarter-wave Instabilitymentioning
confidence: 99%
“…As described in Singh (1983); Urata (1969); Song et al (2013); Darby (2012); Bazsó and Hős (2012) or Allison and Brun (2015), the forces acting on the valve body can be characterized into three forms: force due to pressure distribution, force due to shear stress and impulse forces. In most cases, the shear stress can be neglected because of the small geometry associated with the pipe and hence the relative low Reynolds numbers involved.…”
Section: Valve Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations